The Logic of Impairment in Islamic Law: Philosophical Perspective as a Foundation for Ethics Education - Wahid, Sahid; Musyahid, Achmad; HL, Rahmatiah (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The logic of harm in Islamic Law plays a central role in balancing benefit (benefit) and harm (loss). The principle of lā ḍarara wa lā ḍirāra is an important basis for establishing legal policies that aim to avoid all forms of harm to individuals and society. In the context of Islamic legal philosophy, the logic of harm reflects ethical principles aimed at maintaining human welfare and preventing loss. This article examines the logic of harm as a philosophical framework in determining Islamic law and its application in various aspects of modern life. The research method used is a qualitative research approach with analytical descriptive methods. The approach used by researchers in solving existing problems is normative and theoretical. This research explores the importance of the logic of harm in Islamic Law, especially in maintaining a balance between benefits and harms in various aspects of life. With the principle